The effect of planning policies and practices on the growth and development of black businesses: a case study of Leicester - Dale, Mark Brian (1989)
The purpose of this project was to establish whether or not the development of black owned businesses has been impeded by policies and practices in environmental planning. This question was explored in a series of operational hypotheses using data collected in Leicester for the period 1971-81. The main sources of data were a large sample of planning applications records and an extensive survey of businesses who had applied for planning permission since 1984.